Pseudonannolene lundi n. sp., a new troglobitic millipede from a Brazilian limestone cave (Spirostreptida: Pseudonannolenidae) - Iniesta, Luiz Felipe Moretti; Ferreira, Rodrigo Lopes (Zootaxa, 2015)
Pseudonannolene lundi n. sp., is described from Lapa Sem Fim Cave, a limestone cave from Luislândia municipality, Minas Gerais State, Brazil. The species is the eighth troglobitic millipede and the third of the genus Pseudonannolene described from Brazilian caves. Pseudonannolene lundi shows pronounced depigmentation and decrease of body size, as found in other troglobitic species belonging to the genus. The gonopod has a robust and evident internal branch, and a solenomere slightly trianguliform.